Effects of vibration, vacuum, and material thickness on infrared drying of Cissus quadrangularis Linn. - Setthawat Thanimkarn; Ekkapong Cheevitsopon; Jiraporn Sripinyowanich Jongyingcharoen (My University, 2019)
Infrared (IR), vibratory bed assisted infrared (VIR), vacuum infrared (VC-IR), and vibratory bed assisted vacuum infrared (VC-VIR) drying of Cissus quadrangularis Linn. (CQ) were conducted. The objective was to investigate the effects of vibration, vacuum, and material thickness on IR drying of CQ. VC-VIR drying of 5-mm CQ provided the highest maximum drying rate (DR) of 0.258 g water/g dry matter·min. Although the vacuum operation contributed to improved effective moisture diffusivity (Deff ), it consumed high energy and degraded active compounds of CQ. VIR drying could be a more promising technique. VIR drying of 15-mm CQ produced the greatest total phenolic content (TPC) and quercetin content of 1083.62 mg GAE/100 g dry matter and 3.472 mg/100 g dry matter, respectively. The lowest total color difference (ΔE) of 13.69 was also obtained. It required low specific energy consumption (SEC) of 17.62 kWh/kg and provided maximum DR of 0.112 g water/g dry matter·min.
Keywords: Vacuum drying; Phytochemicals and Antioxidant Activities